Variasi Konsentrasi Bahan Pengikat Dari Pati Biji Durian (Durio Zibethinus)Terhadap Mutu Fisik Pada Formulasi Tablet Hisap Vitamin C - Nur Ain Thomas; Fika Nuzul Ramadhani; Juliyanti Akuba; Ariani H. Hutuba (Journal Syifa Sciences and Clinical Research, 2022)
Starch of durian (Durio Zibethinus) seed is an accessible potential material to be utilized as binding agent in tablet. This study attempts to discover the influence of starch concentrate of durian seed in different percentages, i.e., 20%, 25%, and 30%, as binding agent towards the physical quality (by conducting tests i.e. weight uniformity test, hardness test, friability test, dissolution test, and organoleptic evaluation) towards vitamin C lozenges tablet formulation. Three formulae with different durian seed concentrate variation of F1 (20%), F2 (25%), and F3 (30%) were applied during the formulation of vitamin C lozenges. The result indicates that F2 and F3 formulae fulfilled all the test conducted, while the F1 formula only passed the weight uniformity test, taste response test, and organoleptic test. Based on the results of the study, F3 fulfilled all evaluations carried out, namely F3 4.07 kg hardness test, 0.30% friability test, 443.3 seconds dissolution test. F2 hardness test 3.79 kg, fragility test 0.34% solubility test 402 seconds. F1 hardness test 3.17 kg, fragility test 1.33%, soluble time test, 302.3 seconds. the conclusion obtained from the ANOVA-One way test is that there is a significant disintegration time difference of all formulas and continued by the Post-Hoct test to see the comparison of each formula with a confidence level (95%).